2016
DOI: 10.1136/emermed-2014-204455
|View full text |Cite
|
Sign up to set email alerts
|

Predicting admission at triage: are nurses better than a simple objective score?

Abstract: GAPS, a simple clinical score, is a better predictor of admission than triage nurses, unless the nurse is sure about the outcome, in which case their clinical judgement should be respected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 26 publications
0
18
1
Order By: Relevance
“…We knew from a previous study that GAPS’ receiving operator characteristic (ROC) would have an area under the curve (AUC) of about 0.85 14. Our database suggested that the correlation coefficient of GAPS and Ambs was approximately −0.4, with the ratio of discharges to admissions in our sample being close to 1.5.…”
Section: Methodsmentioning
confidence: 69%
See 2 more Smart Citations
“…We knew from a previous study that GAPS’ receiving operator characteristic (ROC) would have an area under the curve (AUC) of about 0.85 14. Our database suggested that the correlation coefficient of GAPS and Ambs was approximately −0.4, with the ratio of discharges to admissions in our sample being close to 1.5.…”
Section: Methodsmentioning
confidence: 69%
“…As with any such clinical tool, however, its purpose is to support rather than supplant human judgement; previous work has indicated that combining GAPS with a veto from triage nurses would provide an accurate strategy for bed management 14. We suggest that future work should focus on implementation of this approach and impact on ‘front door’ performance.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…These findings suggest that GAPS could be used to help inform clinicians and patients themselves of likely outcomes at an early stage in their hospital visit. GAPS could be utilised to improve flow in the ED, for example, by directing low-risk patients to an ambulatory emergency care facility or urgent clinic, by giving junior clinicians a clearer idea of prognosis to support discharge decisions or by directing senior clinicians to the patients to whose care they are most likely to add the most value 28–30…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, GAPS has been found to be an accurate predictor of patient disposition and has been found to be superior to triage nurses’ ability to predict admission at the point of triage. In addition, GAPS is currently being used at a number of UK sites, including Glasgow, Sheffield, Nottingham and Torbay, to aid in patient streaming in the ED 28–30…”
Section: Introductionmentioning
confidence: 99%